2012
DOI: 10.1111/j.1601-183x.2012.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

COMT val158met predicts reward responsiveness in humans

Abstract: A functional variant of the catechol-O-methyltransferase (COMT) gene [val158met (rs4680)] is frequently implicated in decision-making and higher cognitive functions. It may achieve its effects by modulating dopaminerelated decision-making and reward-guided behaviour. Here we demonstrate that individuals with the met/met polymorphism have greater responsiveness to reward than carriers of the val allele and that this correlates with risk-seeking behaviour. We assessed performance on a reward responsiveness task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 40 publications
10
59
0
Order By: Relevance
“…In one study, DAT1 10-repeat homozygotes exhibited greater risk-taking behavior than 9-repeat carriers (Mata et al, 2012). Another study showed that COMT-met homozygotes took greater risks and subsequently earned more than val carriers (Lancaster et al, 2012). Here, we show that the number of balloon pumps were not significantly related to DAT1 and COMT genotypes or to the gene.…”
Section: Discussionmentioning
confidence: 47%
“…In one study, DAT1 10-repeat homozygotes exhibited greater risk-taking behavior than 9-repeat carriers (Mata et al, 2012). Another study showed that COMT-met homozygotes took greater risks and subsequently earned more than val carriers (Lancaster et al, 2012). Here, we show that the number of balloon pumps were not significantly related to DAT1 and COMT genotypes or to the gene.…”
Section: Discussionmentioning
confidence: 47%
“…Subjects with Val-homozygosity of COMT coupled with the 10R-allele of DAT1 or the opposite profile (Met-homozygosity coupled with the 9R-allele) showed normal to high increases in ventral striatal activation during the anticipation of increasingly higher and more likely rewards indicative of normal to higher behavioral activation, whereas genotype groups in which mesolimbic DA was not in balance with PFC DA (Met-/10R-allele and Val-/9R-allele) showed blunted striatal activity to increasingly higher and more likely rewards (Yacubian et al, 2007). With respect to previous findings, heightened BAS and reward-cue reactivity in Val/10R genotypes may reflect a particular hyperfocus to immediate rewards and increase the risk for impulsivity and externalizing disorders when effortful self-control is lacking (dysfunctional impulsivity) (Hundt et al, 2008;Claes et al, 2009;Congdon et al, 2009;Kimbrel et al, 2012), whereas in Met/9R-carriers, heightened BAS and reward reactivity may represent a general drive to strategically maximize rewards (functional impulsivity) (Smillie and Jackson, 2006;Lancaster et al, 2012). Taken together, Val-homozygosity may especially increase the risk for dysfunctional impulsivity in A1-carriers, especially in the context of 10R-homzygosity for DAT1.…”
Section: Val-homozygotes)mentioning
confidence: 48%
“…Since both Met-and Val-homozygosity have been related to increased striatal DA activations to reward-feedback or reward-predictive cues (Yacubian et al, 2007;Dreher et al, 2009;Camara et al, 2010;Lancaster et al, 2012;Katz et al, 2014), immediate response bias/delay discounting (Boettiger et al, 2007;Paloyelis et al, 2010;Gianotti et al, 2012;Smith and Boettiger, 2012), impulsivity (Salo et al, 2010;Groleau et al, 2012;Varga et al, 2012;Malloy-Diniz et al, 2013;Soeiro-DeSouza et al, 2013;Guillot et al, 2014), and aggression (Rujescu et al, 2003;Caspi et al, 2008;Albaugh et al, 2010;Wagner et al, 2010;Brennan et al, 2011), the effect of COMT genotypes on disinhibitory traits is likely modulated by other factors such as tonic striatal DA activity and D2-receptor densities. For example, Reuter et al (2006) demonstrated that BAS scores correlate with the relative ratio between PFC DA activity as mediated by COMT and striatal DA activity/D2-receptor functioning as mediated by the TaqIA-ANKK1 SNP.…”
Section: Da Metabolization (Catechol-o-methyltransferase)mentioning
confidence: 98%
“…For example, carriers of genetic polymorphisms of COMT val158met (the enzyme catechol-O-methyltransferase, responsible for the degradation of dopamine in the synaptic cleft), the Met/Met and Val/Val, show different behavior in tasks that rely on dopaminergic transmission. Individuals with the Met allele, characterized by higher availability of prefrontal dopamine, showed significantly higher reward responsiveness in a reward-based probabilistic classification task, as well as higher risk taking in the Balloon analogue risk task 1 (Lancaster et al, 2012). This genetic polymorphism was also found to be associated with better suppression of interfering memories, resulting in more efficient remembering (Wimber et al, 2011), pinpointing the role of (prefrontal) dopamine in both reward and memory functions.…”
Section: Individual Differences In Reward Sensitivitymentioning
confidence: 86%